Children’s Ethno-National Flag Categories in Three Divided Societies - Dautel, Jocelyn B. (Journal of cognition and culture, 2020)
Abstract Flags are conceptual representations that can prime nationalism and allegiance to one’s group. Investigating children’s understanding of conflict-related ethno-national flags in divided societies sheds light on the development of national categories. We explored the development of children’s awareness of, and preferences for, ethno-national flags in Northern Ireland, Kosovo, and the Republic of North Macedonia. Children displayed early categorization of, and ingroup preferences for, ethno-national flags. By middle-childhood, children’s conflict-related social categories shaped systematic predictions about other’s group-based preferences for flags. Children of minority-status groups demonstrated more accurate flag categorization and were more likely to accurately infer others’ flag preferences. While most Balkan children preferred divided versus integrated ethno-national symbols, children in the Albanian majority group in Kosovo demonstrated preferences for the new supra-ethnic national flag. We discuss the implications of children’s ethno-national flag categories on developing conceptualizations of nationality and the potential for shared national symbols to promote peace.